Effect of Synthesis Methods Using Renewable PODFA on Structural Characteristics of Metal-Organic Framework (MOF-5) - Othman S.Z.; Misran H.; Affendy W.A.; Mahadi N.F. (Institute of Physics Publishing, 2023)
Alcohols; Crystalline materials; Mixing; Morphology; Organometallics; Palm oil; Pressure vessels; Surface active agents; Direct mixing method; Faceted structures; Metal organic framework; Microwave assisted synthesis; Microwave-assisted methods; Non-surfactant Template; Structural characteristics; Synthesis method; Java programming language; alcohol; numerical method; surfactant; temperature gradient; vegetable oil